A produção acadêmica nos cursos de pós-graduação stricto sensu em Ciências Contábeis com enfoque nas disciplinas de tecnologia da informação - Oliveira, Edson de (2021)
Since 2008, Accounting in Brazil has undergone several changes, both due to the harmonization of Brazilian accounting standards with the international accounting standard, through the International Financial Reporting Standards (IFRS) and due to changes in higher education and especially in courses stricto sensu in Accounting Sciences. Specifically, it brought to Higher Education Institutions – IES – in Brazil a new perspective in relation to teaching for the 28 postgraduate courses in Accounting Sciences. Along with the evolution of international accounting standards, accounting companies and professionals, information technology tools, agility, speed and assertiveness favored the generation of data and information for decision making. Therefore, it was defined as a general objective to analyze data on academic production, through Information Technology (IT) disciplines, in stricto sensu postgraduate courses in Accounting, in the 2017-2020 quadrennium. After the scientific research, it was identified that the stricto sensu courses in accounting sciences include more recent issues regarding the tools used in companies in the disciplines that address IT, both in the master's and doctoral programs, since the purpose of the PPGCC in HEIs is to meet the needs of market demands to which accounting students and professionals are subject to the competitiveness demanded by globalization. The contribution of the research consists in enabling a reflection on the need for technology and innovation to be approached in a transversal way in the courses, forming even more competitive professionals